Time inconsistency in environmental policy: Tax earmaking as a commitment solution - Laura Marsiliani; Thomas I. Renström (Fondazione Eni Enrico Mattei (FEEM), 1999)
Tax earmarking imposes a constraint on government policymaking, and may be desirable if it solves a time-inconsistency problem in tax policy. In a two-period economy, in which the policy decisions regarding taxes, public goods provision, and pollution abatement are taken by a majority-elected individual, we show how the time-inconsistency problem in environmental policy arises. We demonstrate that the commitment equilibrium under no earmarking rules cannot be as fully implemented as a no-commitment equilibrium under earmarking rules. However, the earmarking rules do act as a partial commitment mechanism.
Keywords: D62; D72; E62; H20; 330; Tax earmarking; fiscal policy; redistributive taxation; endogenous taxation; time inconsistency; environmental tax; pollution abatement